Designing Education Experiences with Horses to Develop Social Skills and Emotional Wellbeing: Supporting the Most Vulnerable - Solvason, Carla; Winwood, Jo (Journal of Education and Learning Environments, 2025)
The benefits of horse riding as a form of physical exercise, particularly for those with disabilities, are well known. However, what is less well known is the socio-emotional benefits of time spent in company with horses. This research focuses on a therapeutic equine care club for young people and adults with impairments, developed on the concept of participants volunteering to look after the horses. In the UK, horse-riding is an expensive hobby, inaccessible to many. This club, situated at a state-of-the-art inclusive equestrian centre, and funded by the Commonwealth Games, provided an opportunity to engage in the care of horses for those with learning, developmental, physical, or socio-emotional impairments, free of charge. This research explores the views of those who ran the club, as well as the attendees and their carers. Our findings suggest that time spent in the company of horses, even if limited to groundwork, can have considerable impact upon the development of those who typically struggle with social interaction and emotional regulation. Friendships were formed and challenges overcome in the company of these majestic animals. We conclude that much more could be done to improve the lives of the excluded, disabled, and disengaged, by using horses as a catalyst for motivation and interaction.